1992
DOI: 10.1128/jb.174.3.807-814.1992
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Bacillus megaterium and Bacillus subtilis mutants which lack the protease that degrades small, acid-soluble proteins during spore germination

Abstract: During germination of spores of Bacillus species the degradation of the spore's pool of small, acid-soluble proteins (SASP) is initiated by a protease termed GPR, the product of the gpr gene. Bacillus megaterium and B. subtilis mutants with an inactivated gpr gene grew, sporulated, and triggered spore germination as did gpr+ strains. However, SASP degradation was very slow during germination ofgpr mutant spores, and in rich media the time taken for spores to return to vegetative growth (defined as outgrowth) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 25 publications
4
84
0
Order By: Relevance
“…The results described in this paper also implicate ␣/␤-type SASP in protecting the germinating and outgrowing spores from DNA damage, since the mutation frequency was higher in outgrown ␣ Ϫ ␤ Ϫ spores than in outgrown wild-type spores and was significantly increased in ␣ Ϫ ␤ Ϫ spores by mutations in nfo and exoA. However, the resistance conferred by ␣/␤-type SASP to dormant spores against several DNA-damaging factors is ultimately lost during spore outgrowth (17,23,24), and thus the protective effect postulated here would operate only until ␣/␤-type SASP are degraded by the specific germination protease germination protease in outgrowth (21,28). Indeed, spore resistance to UV radiation persists well after the initiation of spore germination (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results described in this paper also implicate ␣/␤-type SASP in protecting the germinating and outgrowing spores from DNA damage, since the mutation frequency was higher in outgrown ␣ Ϫ ␤ Ϫ spores than in outgrown wild-type spores and was significantly increased in ␣ Ϫ ␤ Ϫ spores by mutations in nfo and exoA. However, the resistance conferred by ␣/␤-type SASP to dormant spores against several DNA-damaging factors is ultimately lost during spore outgrowth (17,23,24), and thus the protective effect postulated here would operate only until ␣/␤-type SASP are degraded by the specific germination protease germination protease in outgrowth (21,28). Indeed, spore resistance to UV radiation persists well after the initiation of spore germination (21).…”
Section: Discussionmentioning
confidence: 99%
“…However, the resistance conferred by ␣/␤-type SASP to dormant spores against several DNA-damaging factors is ultimately lost during spore outgrowth (17,23,24), and thus the protective effect postulated here would operate only until ␣/␤-type SASP are degraded by the specific germination protease germination protease in outgrowth (21,28). Indeed, spore resistance to UV radiation persists well after the initiation of spore germination (21). A recent study revealed that loss of ExoA and Nfo did not sensitize growing cells or wild-type or ␣ Ϫ ␤ Ϫ spores to H 2 O 2 and t-butylhydroperoxide (20).…”
Section: Discussionmentioning
confidence: 99%
“…Following the activation of these receptors, spores release dipicolinic acid, calcium and amino acids (Moir, 2006;Setlow, 2003). Subsequently, the core of the spores becomes hydrated, and the spore cortex and sporespecific proteins are hydrolysed (Chirakkal et al, 2002;Sanchez-Salas et al, 1992;Setlow & Waites, 1976). Approximately 30 min after addition of germinants, the newly formed vegetative cells start to divide (Levinson & Hyatt, 1966;Setlow, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…If, as I have suggested in this review, A-like DNA can exist in vivo, why has it not been seen in other systems? The answer is probably that it rarely exists in significant amounts, because the presence of A-like DNA (or at least a/p-type SASP bound to the A-like DNA) results in drastic reductions in RNA synthesis and therefore cell growth, and in the case of E. coli results in increased spontaneous mutation and often cell death (Sanchez-Salas et al, 1992;Setlow et ai., 1991;Setlow, J.K., Setlow, B., and Setlow, P., unpublished results). Conversion of a cell's genome to an A-like conformation in a dormant bacterial spore, in which gene expression as well as metabolic activity is absent, may not present such a risk.…”
Section: Does A-dna Exist In Iiving Ceiis?mentioning
confidence: 99%